Pengaruh partisipasi anggaran, informasi asimetri, dan kapasitas individu terhadap budgetary slack pada skpd pemerintah kota samarinda - Akhmad Azmi Basyir (Faculty of Economics and Business Mulawarman University, 2016)
Budgeting in public sector is heavily influenced by non economic factors, for example budget participation, asymmetry information, and individual capacity. The purpose of this study was to determine signficant level and the way effect of budget participation, asymmetry information, and indivudual capacity to budgetary slack in SKPD of Goverment Samarinda City. Sample of this study are 148 respondent from 37 agency of SKPD Samarinda City. Only 120 respondent can be procced. Questionnaire were distributed to respondent who had position as head of agency, secretary agency, head financial sub section, and head planing sub section from each agency in SKPD of Goverment Samarinda City. This study using Partial Least Square (PLS) to analysed data. The study concluded that budget participation does have significant and positive influence with the budgetary slack in SKPD of Goverment Samarinda City, therefore Ha1 accepted. while, asymmetry information has significant and positive influence with budgetary slack in SKPD of Goverment Samarinda City, therefore Ha2 accepted. and individual capacity has significant and positive influence with the budgetary slack in SKPD Goverment of Samarinda City, therefor Ha3 accepted.Keyword: Budget Participation, Asymmetry Information, Individual Capacity, and Budgetary Slack.